Testing the effect of display organization in the collinear search impairment. (September 2022) - Jingling, Li; Shioiri, Satoshi
Previous studies established that a salient collinear structure impairs local visual search. A display organization hypothesis states that the vertical grouping of elemental bars in the search display may selectively increase the salience of the local target in the background than that in the collinear distractor, leading to the collinear search impairment. Three displays were designed to test this hypothesis. A classical search display was adopted as a baseline. A diagonal search display was created with tilted bars, making perceptual organization diagonal and should reduce collinear search impairment. An illusory search display was designed by using abutting line illusion to emphasize the vertical grouping direction, which should increase collinear search impairment. A manipulation check was conducted with an online survey to understand the perceptual organization of the three displays. Results showed that the probability to perceive the stimuli grouping in the vertical direction was strongest in the illusory display and the least in the diagonal display. Nevertheless, the collinear search impairment did not vary with these manipulations, argue against the display organization hypothesis. We speculate that the search impairment might associate with the perceptual organization of the collinear distractor per se, rather than the perceptual organization of the background.